Google Classroom utilization and mathematics performance of teacher education students - Gaganao, Rovinson D.; Odon, Ma. Gracelda B. (Intelektual Pustaka Media Utama, 2026)
Google Classroom can enhance the teaching process and support students’ learning. Hence, this study determines the effectiveness of Google Classroom on the respondents’ mathematics performance. The study utilized 159 first-year teacher education students at Eastern Samar State University-Salcedo, selected by stratified random sampling, descriptive-comparative and correlational research design, and a questionnaire. For descriptive analysis, frequency, percentage, mean, and standard deviation were used, as t-test, ANOVA, and Pearson’s correlation coefficient for comparison and relationship between variables. The study revealed that respondents owned a smartphone, which they used to connect to the internet at home and spent 1-2 hours doing internet-related activities. Respondents perceived Google Classroom as a highly effective tool for mathematics, and they had a good to excellent level of mathematics performance. Furthermore, respondents do not significantly differ in their mathematics performance based on their technological profile except for ownership of technology devices. Lastly, the study found that Google Classroom can improve students’ mathematics performance. Based on the findings, it is recommended that Google Classroom be integrated into mathematics as a teaching and learning tool.